Correlating pH and Swelling Degree Parameters to Understand the Sorption and Desorption Process of Diquat Herbicide from Nanocomposites Based on Polysaccharide and Clinoptilolite - Tanaka, Fabrício C. [UNESP]; Junior, Carlos. R. F. [UNESP]; Fernandes, Renan. S. [UNESP]; de Moura, Marcia R. [UNESP]; Aouada, Fauze A. [UNESP] (Springer Nature, 2021)
Zeolite-based nanocomposites have become an efficient option for application in herbicide removal and controlled release systems. Our group previously described the degree of swelling in water and salt solutions, spectroscopic and structural properties, and fertilizer desorption from carboxymethylcellulose-poly(methacrylic acid-co-acrylamide)-zeolite nanocomposites. Here, morphological and thermal properties, and swelling degree studies at different pH was investigated in these same nanocomposites. Their water-uptake in these various swelling media was correlated with sorption and desorption profiles of diquat. SEM-EDX technique indicated the presence of zeolite in the nanocomposites, as well as the increase in the quantity of water hydration molecules trapped in the zeolite cavities was confirmed by DSC. Improved diquat sorption from 8.3 to 9.4 mg/g was recorded when 1.5% zeolite was added into nanocomposites, indicating a significant increase in herbicide–matrix interaction. This increase also led to a small decrease in the desorption process, but in a more controlled manner. Variation of pH of the swelling media might have changed the elasticity of nanocomposite chains, which in turn adjusted release rate. A better understanding of nanocomposite–herbicide interaction can help design novel matrices with enhanced pesticide sorption, contributing to reduce contaminations caused by the indiscriminate use of agrochemicals.
Keywords: Hydrogels; Nanocomposites; Polysaccharides; UV–Vis spectroscopy; Zeolites